2000
DOI: 10.1046/j.1365-2141.2000.02267.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between bleeding time, aspirin and the PlA1/A2 polymorphism of platelet glycoprotein IIIa

Abstract: Summary. A single nucleotide T to C transition of the gene encoding glycoprotein IIIa leads to a common diallelic polymorphism Leu-333Pro (PLA1/A2). We studied the relationship between the PlA1/A2 polymorphism and platelet function in 80 healthy men, aged 20±25 years. Before aspirin ingestion, bleeding time (BT) was shorter in carriers of the PlA2 than in carriers of the PlA1/A1 allele. At 4 h after ingestion of 300 mg of aspirin, BT became prolonged, and the intergroup difference was enhanced. In seven out of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(77 citation statements)
references
References 14 publications
3
70
0
2
Order By: Relevance
“…Concerning platelet membrane glycoproteins, it has been reported that genetic polymorphisms of GPIa, 10 GPIba, 11 GPIIIa 12,13 and GPVI 14 influence the efficacy of aspirin or platelet responsiveness. Furthermore, Halushka et al 15 reported the association of platelet aggregation with genetic mutation of COX-1, Papafili et al 16 the association with genetic mutation of COX-2, Higuchi et al 17 the association with genetic mutation of TXA 2 receptors (TP), Stafforini et al 18 the association with genetic mutation of platelet activating factor acetylhydrolase (PAFAH) and Undas et al 19 the association with genetic mutation of coagulation factor XIII (FXIII).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning platelet membrane glycoproteins, it has been reported that genetic polymorphisms of GPIa, 10 GPIba, 11 GPIIIa 12,13 and GPVI 14 influence the efficacy of aspirin or platelet responsiveness. Furthermore, Halushka et al 15 reported the association of platelet aggregation with genetic mutation of COX-1, Papafili et al 16 the association with genetic mutation of COX-2, Higuchi et al 17 the association with genetic mutation of TXA 2 receptors (TP), Stafforini et al 18 the association with genetic mutation of platelet activating factor acetylhydrolase (PAFAH) and Undas et al 19 the association with genetic mutation of coagulation factor XIII (FXIII).…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have reported that carriers of the PlA2 polymorphism appeared to be more resistant to aspirin than did noncarriers; in particular, PlA2 homozygosity has been associated with an inadequate response to aspirin (40)(41)(42). However, due to the retrospective nature of the study and the low number of patients included in the analysis, the results of the present study should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 40%
“…18 Finally, carriers of Pl A2 receiving aspirin have a blunted bleeding time response. 19 However, other studies have failed to show any enhanced effect. [20][21][22] Patients, materials, and methods…”
mentioning
confidence: 94%